TWO-STAGE SURGICAL TREATMENT OF A CHILD OF ONE YEAR FROM CONGENITAL HEART DISEASE AND BILIARY CIRRHOSIS - S. V. Gautier; A. S. Ivanov; V. N. Poptsov; O. M. Tsirulnikova; S. V. Glamazda; A. S. Rodionov; A. V. Lebedeva; H. M. Hizroev; D. G. Ahaladze; M. K. Lugovskiy; I. V. Zhilkin (Вестник трансплантологии и искусственных органов)
Aim: Clinical case of successful two-stage surgical treatment of a 1-year-old child with congenital heart disease and biliary cirrhosis is represented in this article. At the first day of life laparotomy was performed because of high intestinal obstruction. Kasai procedure and Roux-en-Y choledochojejunostomy were per- formed on 12th day and at the end of second month of life, respectively. Liver biopsy showed the signs of biliary cirrhosis. At the same time ventricular septal defect and atrial septal defect with pulmonary hyper- tension were diagnosed. The first step of treatment was the surgical septal defects closure. No complications during procedure, cardiopulmonary bypass and post-operative period were registered. There were no nega- tive effects on liver function after cardiac surgery. 11 months later living-donor liver transplantation was performed without any complications. Patient was discharged at 35th post-transplant day with stable graft function.